Does breastfeeding have a long-term positive effect on dental occlusion? - Boronat-Catalá, Montserrat (J Clin Exp Dent, 2019)
BACKGROUND: Breastfeeding produces beneficial effects on a baby’s early growth and development, and general well-being. Some studies have associated breastfeeding with better occlusal development. The aim of this study was to assess the long-term effect of breastfeeding on occlusal development in children. MATERIAL AND METHODS: A retrospective cohort study was conducted to evaluate the occlusions of 320 children belonging to the Spanish INMA Project cohort, monitored from gestation onwards. The association between the duration of breastfeeding and different occlusal traits in mixed dentition (overjet, overbite, openbite, midline displacement, incisor crowding, incisor spacing, diastema, maximum maxillary and mandibular irregularity, anterior and posterior crossbite) at the age of 9 was assessed, as well as the orthodontic treatment need as determined by the “Index of Orthodontic Treatment Need” and the “Dental Aesthetic Index”. RESULTS: A statistically significant association between the duration of breastfeeding and posterior crossbite was found. The Odds Ratio for posterior crossbite was 2.52 (IC 95% 1.34-4.74) for children breastfed up to 16 weeks, 0.56 (IC 95% 0.29-1.08) for children breastfed 16 to 45 weeks, and for more than 45 weeks of breastfeeding it was 0.50 (IC 95% 0.19-1.32). No association was found between breastfeeding and the other examined occlusal traits, nor with the orthodontic treatment need. CONCLUSIONS: Breastfeeding for less than 4 months increases the risk of posterior crossbite. However, breastfeeding duration is not linked to other malocclusion traits nor is it linked to the orthodontic treatment need of nine-year-old children. Key words:Breastfeeding, occlusion, malocclusion, dental development.